AN EXPERIMENTAL STUDY OF VCL AND CSCL TO ENHANCE STUDENTS’ LEARNING ACHIEVEMENT AND ENGAGEMENT IN CHEMISTRY - Tamusuza, Dean; Chalermnirundorn, Nipaporn (วารสารวิชาการ มหาวิทยาลัยราชภัฏพระนคร, 2018)
Virtual Chemistry Labs (VCLs) are among the emerging technologies being used in education today. Of the various educational uses of this pedagogy, the focus of this research targeted two objectives; first, comparing the students learning achievement using VCL together with computer-supported collaborative learning (CSCL) to that of real labs (RL) and secondly investigating students’ learning engagement using VCL together with CSCL. A quantitative research method mixed with a qualitative study was used to measure the students’ learning achievement and engagement respectively during chemistry lessons. The results of the post-test indicated that students’ learning achievement significantly increased after performing virtual chemistry lab experiments. The average post-test mean score of the experimental group was 34.25 as opposed to pre-test 26.65 before VCL and CSCL were applied to carry out the study. The significance level obtained from comparing post-tests of the two groups was 0.000. This is a statistically significant figure implying that the experimental group had a better performance from the post-tests than the control group. Similarly, observation results also indicated student engagement. In fact, 80% of the time was spent by students actively engaged in VCL activities and collaboratively working together with their peers. In addition to this research, possible directions for further research in the use of VCL were discussed.